Tools for determining critical levels of atmospheric ammonia under the influence of multiple disturbances (Environmental Pollution, 2014)
Critical levels (CLEs) of atmospheric ammonia based on biodiversity changes have been mostly calculated using small-scale single-source approaches, to avoid interference by other factors, which also influence biodiversity. Thus, it is questionable whether these CLEs are valid at larger spatial scales, in a multi- disturbances context. To test so, we sampled lichen diversity and ammonia at 80 sites across a region with a complex land-cover including industrial and urban areas. At a regional scale, confounding factors such as industrial pollutants prevailed, masking the CLEs. We propose and use a new tool to calculate CLEs by stratifying ammonia concentrations into classes, and focusing on the highest diversity values. Based on the significant correlations between ammonia and biodiversity, we found the CLE of ammonia for Mediterranean evergreen woodlands to be 0.69 mgm?3, below the previously accepted value of 1.9 mgm?3, and below the currently accepted pan-European CLE of 1.0 mgm?3

Causes of change in nitrophytic and oligotrophic lichen species in a Mediterranean climate: impact of land cover and atmospheric pollutants. (Environmental pollution (Barking, Essex : 1987), 2008)
With the aim of determining the main drivers of changes in nitrophytic and oligotrophic macro-lichen communities in an industrial region with a Mediterranean climate, we considered both land-cover types and atmospheric pollutants. We determined the relation between the abundance of nitrophytic and oligotrophic species with environmental factors considering the distance of influence of land-cover types. The results showed that oligotrophic species decreased in the proximity of artificial areas, barren land and agricultural areas, associated with higher concentrations of NO2 and Zn, and Ti, probably dust of industrial and agricultural origin. Nitrophytic species were positively related to all the mentioned land-cover types, and with higher concentrations of Fe and N. Magnesium, probably from ocean aerosols, was negatively related to oligotrophic species and positively to nitrophytic.

Improving the use of lichens as biomonitors of atmospheric metal pollution. (The Science of the total environment, 1999)
The data reported on this study supported the hypothesis that the absence of the lichen Ramalina fastigiata near a copper mine site located on the south of Portugal was related to toxic levels of Cu-dust near the centre of the mine. Lichen biodiversity reflected the impact of the copper-mine dust emissions which were more widespread towards the east, correlated with wind direction and frequency. The chemical analysis of R. fastigiata collected at different distances and in different directions from the mine showed that Cu, K and Mg were derived from the centre of the mine site, confirming thus as the major source of atmospheric dust. Total inhibition of PSII photochemical reactions occurred in R. fastigiata both under field and controlled conditions, when intracellular Cu concentrations exceeded a threshold of approximately 2.0 mumol g-1. No samples of this species were found under field conditions beyond the Cu threshold. Thus, the fluorescence parameter Fv/Fm proved to be a good estimator of the survival capacity of R. fastigiata under field conditions and thus a useful parameter in determining the sensitivity of the lichens (photobiont) to Cu pollution. The intracellular location of Cu allowed an explanation of the physiological changes and the survival of the species in the surroundings of the copper-mine.